BsdA(Bsd2) -dependent vacuolar turnover of a misfolded version of the UapA transporter along the secretory pathway: Prominent role of selective autophagy. - Evangelinos, Minoas; Martzoukou, Olga; Chorozian, Koar; Amillis, Sotiris; Diallinas, George (Mol Microbiol, 2016)
Transmembrane proteins translocate co-translationally in the endoplasmic reticulum (ER) membrane and traffic as vesicular cargoes, via the Golgi, in their final membrane destination. Misfolding in the ER leads to protein degradation basically through the ERAD/proteasome system. Here, we use a mutant version of the purine transporter UapA (ΔR481) to show that specific misfolded versions of plasma membrane cargoes undergo vacuolar turnover prior to localization in the plasma membrane. We show that non-endocytic vacuolar turnover of ΔR481 is dependent on BsdA(Bsd2) , an ER transmembrane adaptor of HulA(Rsp5) ubiquitin ligase. We obtain in vivo evidence that BsdA(Bsd2) interacts with HulA(Rsp5) and ΔR481, primarily in the ER. Importantly, accumulation of ΔR481 in the ER triggers delivery of the selective autophagy marker Atg8 in vacuoles along with ΔR481. Genetic block of autophagy (atg9Δ, rabO(ts) ) reduces, but does not abolish, sorting of ΔR481 in the vacuoles, suggesting that a fraction of the misfolded transporter might be redirected for vacuolar degradation via the Golgi. Our results support that multiple routes along the secretory pathway operate for the detoxification of Aspergillus nidulans cells from misfolded membrane proteins, and that BsdA is key factor for marking specific misfolded cargoes. This article is protected by copyright. All rights reserved.